Pengaruh Emisi Karbon, Inovasi Hijau Terhadap Nilai Perusahaan dengan Moderasi Kinerja Lingkungan - Artika, Maya; Sisdianto, Ersi; Ekawati, Evi (Penerbit Goodwood, 2025)
Purpose: This study aims to explore the influence of carbon emissions and green innovation on firm value, considering environmental performance as a moderating factor. Methodology/approach: This research employs a quantitative methodology, drawing upon secondary sources derived from both Sustainability Reports and Annual Reports. The study focuses on manufacturing firms included in the Indonesian Sharia Stock Index (ISSI) for the years 2021–2023. Results/findings: The results demonstrate that company value is affected by the extent of disclosures concerning carbon emissions and green innovation. However, environmental performance does not function as a moderating factor in the link between carbon emission disclosure, green innovation, and firm value. Islamic law states that any company's everyday activities must include meeting its responsibilities to the community and environment. Conclusion: These findings suggest that firm value is directly influenced by green innovation and the transparency of carbon emission disclosures. However, the correlation between these factors and business value is not substantially strengthened by environmental performance. This finding implies that business initiatives to enhance environmental performance are not yet sufficient to convince investors to change their perception of the risks or benefits associated with carbon emission disclosure and green innovation. Limitations: This study has limitations because it only focuses on 20 primary consumer goods sector manufacturing companies registered with ISSI during the period 2021-2023, so the generalization of the results is limited. Contribution: This research contributes to deepening the comprehension of how carbon emission disclosure and green innovation affect Indonesian companies' worth, as well as the role that complicated environmental performance plays as a moderating factor.